2016
DOI: 10.1111/all.13050
|View full text |Cite
|
Sign up to set email alerts
|

Ana o 3-specific IgE is a good predictor for clinically relevant cashew allergy in children

Abstract: Specific IgE to Ana o 3 is a valuable tool for the diagnosis of cashew allergy. Considering its positive predictive value, it might allow to make a considerable number of oral challenges superfluous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 21 publications
6
62
1
1
Order By: Relevance
“…Sensitization to Ana o 3 is predictive of cashew nut allergy [26]. Studies from Lange et al [15] have shown a probability curve for a positive cashew nut OFC result by Ana o 3. But Ana o 3 can only be measured for research in Japan; therefore examining cashew nut sIgE is useful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitization to Ana o 3 is predictive of cashew nut allergy [26]. Studies from Lange et al [15] have shown a probability curve for a positive cashew nut OFC result by Ana o 3. But Ana o 3 can only be measured for research in Japan; therefore examining cashew nut sIgE is useful.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few reports summarizing the results of OFC for cashew nuts and the risk factors for a positive cashew nut OFC result. Lange et al [15] reported the probability curve of cashew nut specific IgE (sIgE) but there is a possibility that the probability curve may change depending on whether or not the patient has a history of immediate reactions to cashew nuts. Therefore, we analyzed the risk factors for symptom induction during a cashew nut OFC and the probability curve of cashew nut sIgE for patients with or without a history of immediate reactions to cashew nuts.…”
Section: Risk Factors and Clinical Features In Cashew Nut Oral Food Cmentioning
confidence: 99%
“…This pattern of sensitization has been associated with both mild and severe systemic reactions. Serum sIgE to cashew components in children performs better than cashew‐specific IgE or SPT and Ana o 3 appears the best predictor of cashew nut allergy .…”
Section: Diagnosismentioning
confidence: 94%
“…21 Furthermore, the Australian HealthNuts cohort reported that at 12 months only 11% of almond-, 19% of hazelnut-, and 39% of cashew-sensitized patients had a positive OFC. 22 New diagnostic component data have highlighted and supported the clinical value of Cor a 9, Cor a 14 for hazelnut allergy, Jug r 1 for walnut allergy, and Ana o 3 for cashew and possibly pistachio allergy [23][24][25] in addition to well-established peanut data. 26,27 A Europe-wide approach to study hazelnut allergy suggested that combinations of component-resolved diagnosis (CRD)-based approaches with clinical history and extract data are superior to CRD alone.…”
Section: Novel Data On Clinical Markers and Biomarkers Of Food Allergymentioning
confidence: 99%